The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.13080/z-a.2015.102.029
|View full text |Cite
|
Sign up to set email alerts
|

Effect of drying methods on the chemical composition and colour of peppermint (Mentha × piperita L.) leaves

Abstract: The study was done with the two peppermint (Mentha × piperita L.) cultivars -'Krasnodarskaja' and 'Peppermint', whose leaves were dried using different methods. Investigation of fresh and dried herbs was carried out according to the biochemistry and technology methods. Essential oil was extracted using the hydro distillation method, the amount of chlorophyll a and b was measured spectrophotometrically according to the Vernon method. The highest content of essential oil (0.77%) and chlorophyll (1.69%) was found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 22 publications
(20 reference statements)
2
16
0
2
Order By: Relevance
“…The unidentified peaks corresponded to 66.72, 42.12, 37.50, 70.74, and 67.88% of the total peak areas in the rosemary, basil, peppermint, thyme, and oregano extracts, respectively, and require further studies. Polyphenol composition (types and concentrations) of herbs have been reported to be different depending on the harvest times, seasonal variations, and drying conditions (27)(28)(29).…”
Section: Resultsmentioning
confidence: 99%
“…The unidentified peaks corresponded to 66.72, 42.12, 37.50, 70.74, and 67.88% of the total peak areas in the rosemary, basil, peppermint, thyme, and oregano extracts, respectively, and require further studies. Polyphenol composition (types and concentrations) of herbs have been reported to be different depending on the harvest times, seasonal variations, and drying conditions (27)(28)(29).…”
Section: Resultsmentioning
confidence: 99%
“…Khan, H. Zaneb, S. Masood (2016) studied the effect of the extract of the leaves of the Moringaoleifera plant on the morphology of the intestines of broiler chickens. It was noted that the length of the villi in the small intestine and the excretion of mucin increased during the experiments [10], [11].…”
Section: Discussionmentioning
confidence: 94%
“…et al (2016) studied the effect of aqueous extracts of oregano (Origanumvulgare L.) and rosemary (Rosmarinusofficinalis L.) on the immunity and microbial population of the intestines of broiler chickens. Based on the results obtained, it was concluded that extracts of these herbs enhance the immunity of broilers and contribute to the balance of the intestinal flora necessary for digestion and for protection against pathogenic microorganisms [10]- [12].…”
Section: Discussionmentioning
confidence: 99%
“…Improving the existing technologies and developing new effective ones for processing agricultural raw materials has always been one of the urgent tasks of the food industry [1][2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%